2011
DOI: 10.7863/jum.2011.30.6.773
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimates of the Variability of In Vivo Sonographic Measurements of the Mouse Aorta for Studies of Abdominal Aortic Aneurysms and Related Arterial Diseases

Abstract: Objectives Burgeoning interest in reducing the morbidity and mortality associated with abdominal aortic aneurysms (AAAs) has led to experimental strategies to elucidate the disease process and attain pharmacologic regression using the apolipoprotein E−/− (ApoE−/−) mouse model of angiotensin-induced AAAs and in vivo sonography. However, the variability of in vivo sonographic measurements of the mouse aorta has not been established. Thus, our purpose was to determine quantitative estimates of the variability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…Monocyte subsets decreased back to the PBS level after 14 days and remained stable until the end of treatment ( Figure IIA in the online-only Data Supplement), showing that early mobilization of monocyte subsets is transient and may account for early aortic macrophage accumulation during AngII delivery. As a note, 14 days of AngII delivery significantly increased the pool of monocytes in the BM and the spleen, despite no change in the blood ( Figure IIB in the online-only Data Supplement).Despite controlled experimental conditions, the heterogeneity in AAA lesion development reported previously 34 and observed in our hands prompted us to evaluate whether changes in blood monocyte levels could be an indicator of later aneurysm formation ( Figure 2C). We found that in mice that did not develop AAA, monocyte levels remained stable over the course of the experiment and were comparable with monocyte levels observed in response to PBS.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Monocyte subsets decreased back to the PBS level after 14 days and remained stable until the end of treatment ( Figure IIA in the online-only Data Supplement), showing that early mobilization of monocyte subsets is transient and may account for early aortic macrophage accumulation during AngII delivery. As a note, 14 days of AngII delivery significantly increased the pool of monocytes in the BM and the spleen, despite no change in the blood ( Figure IIB in the online-only Data Supplement).Despite controlled experimental conditions, the heterogeneity in AAA lesion development reported previously 34 and observed in our hands prompted us to evaluate whether changes in blood monocyte levels could be an indicator of later aneurysm formation ( Figure 2C). We found that in mice that did not develop AAA, monocyte levels remained stable over the course of the experiment and were comparable with monocyte levels observed in response to PBS.…”
mentioning
confidence: 97%
“…Despite controlled experimental conditions, the heterogeneity in AAA lesion development reported previously 34 and observed in our hands prompted us to evaluate whether changes in blood monocyte levels could be an indicator of later aneurysm formation ( Figure 2C). We found that in mice that did not develop AAA, monocyte levels remained stable over the course of the experiment and were comparable with monocyte levels observed in response to PBS.…”
Section: Angiotensinmentioning
confidence: 99%
“…In the first arm, mice were exposed to 5 mg/kg/week of B(a)P (98 % pure; Sigma) for 42 days, and in the second arm to 0.71 mg/kg/day for 60 days. Benzo(a)pyrene exposure was done via oral gavage, and AngII exposure (1000 ng/kg/min 9 2 weeks) occurred via subcutaneous osmotic mini pumps (Alzet Model 2004, Durect Corporation, CA) as previously described [11]. In the B(a)P ?…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…This measurement also showed that the biggest variation happened in suprarenal and infrarenal segments, which were caused by remodeling as the result of aneurysm and atherosclerosis process. 8,21 Variation also happened in the measurement result by using ultrasound compared with measurement to histologic specimen. Some factors causing this are measurement location may not be exactly the same, since it is impossible to give marker to state measurement location.…”
Section: 56mentioning
confidence: 99%
“…The use of ultrasound to evaluate blood vessels of experimental animal in a research to estimate the abdominal aortic aneurysm regression was initiated by Wang, et al 5 Sampson, et al state that the measurement of in vivo rat's abdominal aortic diameter using high frequency ultrasound shows that the result is not different from that using the in vitro measurement. 8 Another study conducted by Radu et al compared the measurement of ascending aorta using US with 9 MHZ probe with that of video microscopy, and the result shows no difference as well. 9 Blood vessels have walls consisting of three concentric layers, which are tunica intima, tunica media, and tunica adventitia.…”
Section: Introductionmentioning
confidence: 99%